The heat shock protein 90 inhibitor BIIB021 suppresses the growth of T and natural killer cell lymphomas - Suzuki, Michio; Takeda, Tadashi; Nakagawa, Hikaru; Iwata, Seiko; Watanabe, Takahiro; Siddiquey, Mohammed N. A.; Goshima, Fumi; Murata, Takayuki; Kawada, Jun-ichi; Ito, Yoshinori; Kojima, Seiji; Kimura, Hiroshi (Frontiers in Microbiology, 2015)
Epstein-Barr virus (EBV), which infects not only B cells but also T and natural killer (NK) cells, is associated with a variety of lymphoid malignancies. Because EBV-associated T and NK cell lymphomas are refractory and resistant to conventional chemotherapy, there is a continuing need for new effective therapies. EBV-encoded ‘latent membrane protein 1’ (LMP1) is a major oncogene that activates nuclear factor kappa B (NF-kB), c-Jun N-terminal kinase (JNK), and phosphatidylinositol 3-kinase signaling pathways, thus promoting cell growth and inhibiting apoptosis. Recently, we screened a library of small-molecule inhibitors and isolated heat shock protein 90 (Hsp90) inhibitors as candidate suppressors of LMP1 expression. In this study, we evaluated the effects of BIIB021, a synthetic Hsp90 inhibitor, against EBV-positive and -negative T and NK lymphoma cell lines. BIIB021 decreased the expression of LMP1 and its downstream signaling proteins, NF-kB, JNK, and Akt, in EBV-positive cell lines. Treatment with BIIB021 suppressed proliferation in multiple cell lines, although there was no difference between the EBV-positive and -negative lines. BIIB021 also induced apoptosis and arrested the cell cycle at G1 or G2. Further, it downregulated the protein levels of CDK1, CDK2, and cyclin D3. Finally, we evaluated the in vivo effects of the drug; BIIB021 inhibited the growth of EBV-positive NK cell lymphomas in a murine xenograft model. These results suggest that BIIB021 has suppressive effects against T and NK lymphoma cells through the induction of apoptosis or a cell cycle arrest. Moreover, BIIB021 might help to suppress EBV-positive T or NK cell lymphomas via the downregulation of LMP1 expression.